Pola Makan dan Aktivitas Fisik sebagai Faktor Risiko Diabetes Melitus - Khatimah, Husnul; Masdalis, Masdalis; Lestari, Dinda Tri; Wijayaningsih, Kartika Sari (Journal of Telenursing (JOTING), 2025)
This study aims to examine the relationship between diet and physical activity and the incidence of diabetes mellitus. The research method used an analytical survey with a cross-sectional study design. Based on the statistical test results, there was a relationship between diet and physical activity and the incidence of diabetes mellitus, with a p-value of 0.01 (diet) and a p-value of 0.005 (physical activity). In conclusion, a relationship exists between diet and physical activity and the incidence of diabetes mellitus. Irregular diet, consumption of foods high in sugar and fat, and a sedentary lifestyle can increase the body's risk of developing insulin resistance and ultimately lead to a diagnosis of diabetes mellitus.   Keywords: Physical Activity, Diabetes Mellitus, Diet